[18F]RO948 tau PET in bvFTD due to C9orf72 and GRN mutations. (1st February 2022) - Leuzy, Antoine; Santillo, Alexander; Smith, Ruben; Groot, Colin; Ossenkoppele, Rik; Hansson, Oskar
Abstract: Background: The behavioral variant of frontotemporal dementia (bvFTD) is characterized by marked changes in personality and behaviour. Approximately 30% of cases are genetic in nature and most commonly due to autosomal dominant mutations in the chromosome 9 open reading frame 72 ( C9orf72 ) and progranulin ( GRN ) genes resulting in TAR DNA‐binding protein 43 (TDP‐43) pathology. Several tau positron emission tomography (PET) studies using [ 18 F]flortaucipir have shown conflicting results regarding tracer retention in bvFTD due to C9orf72 (bvFTD‐ C9orf72 ) and GRN (bvFTD‐ GRN ) mutations. To date, no studies in bvFTD due to either mutation have been conducted using the novel tau tracer [ 18 F]RO948. Method: Eight patients meeting criteria for definite bvFTD were included from the Swedish BioFINDER‐2 study, including seven C9orf72 expansion carriers and one with a GRN mutation. Standardized uptake value ratio (SUVR) images of [ 18 F]RO948 PET were created using 70‐90 post‐injection data and the inferior cerebellar cortex as reference region. Age and sex matched CU individuals (n=9) and patients with Alzheimer's disease (AD) dementia (n=9) were included for comparison. [ 18 F]RO948 retention in bvFTD mutation carriers was also assessed relative to a larger Aβ‐negative CU group (n=50) using age‐adjusted voxelwise t‐tests. Result: BvFTD‐ C9orf72 patients were on average 63 years of age (range 53‐72) and 57% were female. The bvFTD‐ GRN patient was a 69‐year‐old male. Comparison of SUVR images showed that [ 18 F]RO948 retention levels in bvFTD mutation carriers were similar to those seen in Aβ‐negative CU individuals (Figure 1). Voxelwise t‐tests showed no significant differences in comparison to the Aβ‐negative CU group. Similar findings were seen using a composite frontal region of interest (ROI) and when using the brainstem as reference instead of the inferior cerebellar cortex. Conclusion: These preliminary findings suggest that [ 18 F]RO948 signal is specific for AD‐type tau and does not capture TDP‐43 type pathology.